Experimental and Analytical Study on Postfire Reinforced Concrete Beams Retrofitted with CFRP in Flexure and Shear - Vu Nguyen Nguyen; Vui Van Cao (Civil Engineering Journal, 2023)
In this study, experiments were performed on carbon fiber reinforced polymer (CFRP) retrofitted postfire reinforced concrete (RC) beams, followed by theoretical analyzes. Experiments were conducted on eleven RC beams, which were exposed to different fire durations and retrofitted with CFRP in flexure and shear. The experimental results indicated that fire shifted the flexure failure to the flexure-shear failure of postfire RC beams. CFRP retrofitted postfire RC beams experienced progressive peeling-off failure. FRP retrofitting significantly increased the yield deflection by 58.2−97.3% but decreased the ultimate deflection by 43.0−55.5% compared with that of the control beam. Consequently, the ductility was reduced by 69.7−74.7%, categorized as low ductility. CFRP retrofitting successfully increased the strengths of 30-min postfire beams by up to 23.1% higher than those of the control beam. Fire significantly decreased the stiffness of postfire beams by 46.4−49.2% compared with that of the control beam, whereas CFRP retrofitting did not fully recover the stiffness of postfire beams. Finally, a simple model of the moment capacity of postfire beams without/with CFRP retrofits was developed based on the practicability of limited data feasibly obtained from real fires. The proposed model, with its simplicity, practicability, and reasonable accuracy, can be a useful tool for structural engineers in the FRP retrofitting of postfire RC structures. Doi: 10.28991/CEJ-2023-09-07-05 Full Text: PDF